Imus High School for Agricultural Science - Tabang, Krisha Kyna C. (College of Architecture, University of the Philippines Diliman, 2020)
Architecture is a celebration of identity and change. It creates a nurturing environment that fosters a community's enrichment and growth through collective efforts. The thesis investigates the city of Imus in Cavite and how its rapid urbanization affects its agricultural industry and its community's mindset towards agriculture. The provision of a modern educational facility is seen as a solution not just to address the social needs of the city's growing population, but also as a crucial facility in propagating values in agricultural and environmental education. The study explores possibilities of agriculture being integrated into the urban fabric through schools. The goal of this project is to create an education facility that focuses on teaching the basic skills and values on agriculture and environmental education to the high school students of Imus. It will explore how concepts of sustainability and experiential design can be integrated in Filipino schools. The school shall offer classes that focus on agriculture and research.